COMPARISON OF INDEPENDENT REGIONAL INSTITUTIONS THAT CONSULTATIVE IN THE LOCAL GOVERNMENT SYSTEM - Hadita, Cynthia; Harijanti, Susi Dwi; Afnila, Afnila; Azwar, T. Keizerina Devi (Proceeding International Seminar of Islamic Studies, 2023)
Independent regional institutions as derivatives of independent state institutions or will be studied can regional institutions be formed on the basis of regional needs and regulated in laws and regulations, so that a comparison will be made with France and the United States regarding independent regional institutions that are consultative with those that are implemented or that have not been implemented in the local government system in Indonesia. The research method used is normative juridical. The results showed that Indonesia does not yet have independent regional institutions that are consultative, compared to France and America have independent regional institutions that are consultative so that local/state governments can take appropriate policies.